PELAKSANAAN SUPERVISI AKADEMIK SEBAGAI UPAYA UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN - Rambe, Mangarahon (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by a lack of understanding of teachers in preparing lesson plans in a complete and systematic manner, besides that the ability of teachers is not sufficient in developing the components of lesson plans according to the needs and abilities of students. The purpose of this study is to improve teacher competencies in preparing learning implementation plans through academic supervision. This research is a classroom action research. School action research is carried out in four stages, namely planning, implementation, observation and reflection, and carried out at least in two cycles. The research subjects were mathematics teachers totaling 6 people who were in the shade school of the researchers. The research instruments used were RPP documents and assessment observation sheets. The results of the study showed that the teacher's competence in preparing lesson plans in the first cycle was 40.90% which was included in the less category, in the second cycle it increased to 92.42% which was included in the good category. The conclusion based on the research data is that the teacher's competence in preparing lesson plans has increased after academic supervision.